Experimental testing of a cooperative ASV-ROV multi-agent system. Issue 23 (2016) - Conte, Giuseppe; Scaradozzi, David; Mannocchi, Daniele; Raspa, Paolo; Panebianco, Luca; Screpanti, Laura
Abstract: The development of versatile and cost effective robotic tools for exploration and intervention in the underwater environment is presently a topic of interest in marine engineering. A viable, efficient solution is given by robotic platform that couple autonomous surface vehicles and unmanned underwater vehicles in integrated structures with various levels of cooperation. In this paper, we describe a number of field tests on the surface component of a robotic platform consisting of an autonomous surface vehicle that can automatically deploy and recover a small remotely operated vehicle. The aim of the tests are to assess the main functionality of the navigation, guidance and control system of the vehicle in relation to basic navigation tasks, both in supervised and in fully autonomous mode. In particular, in order to assure cooperation with the deployed remotely operated vehicle, the ability to track a target is considered.